2009
DOI: 10.1248/bpb.32.247
|View full text |Cite
|
Sign up to set email alerts
|

The Anti-stress Effects of Sarcandra glabra Extract on Restraint-Evoked Immunocompromise

Abstract: Sarcandra glabra was a renowned herb traditionally used as herbal tea or food supplement to enhance mental efficiency and to recover from stress or fatigue in China. We investigated the effects of Sarcandra glabra extract (SGE), with chemical composition clearly showed by HPLC fingerprint as quality control, on immunologic response including natural killer (NK) cell activity and its antioxidative capacity in splenocytes obtained from restraint mice. Our results found that daily oral administration of SGE (125,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
49
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 52 publications
(55 citation statements)
references
References 25 publications
5
49
1
Order By: Relevance
“…It was reported that restraint stress in mice changed the number of lymphocyte cells, altered antibodies production, and suppressed cytotoxicity of the NK and T cells. It also indicated that stress can impair immunocompetence via the oxidation process [19,20]. These results support our data by suggesting that the improved immunologic response was possibly due to the antioxidative capacity in the immune cells enhanced by S. muticum intake.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…It was reported that restraint stress in mice changed the number of lymphocyte cells, altered antibodies production, and suppressed cytotoxicity of the NK and T cells. It also indicated that stress can impair immunocompetence via the oxidation process [19,20]. These results support our data by suggesting that the improved immunologic response was possibly due to the antioxidative capacity in the immune cells enhanced by S. muticum intake.…”
Section: Discussionsupporting
confidence: 89%
“…The result of analysis conducted by dividing participants into three groups by lactate concentration (11~16, 17~20, & more than 20) showed that the group with a higher lactate concentration had a remarkable decrease in lactate concentration after S. muticum intake. In particular, it was suggested that S. muticum intake was very effective in lowering serum lactate concentration in the group with a high level of fatigue or in people with great stress.…”
Section: Discussionmentioning
confidence: 99%
“…Research has proved that immune functions were commonly lower in organisms under stressed conditions (1,2). It has been shown that stress is strongly associated with the development of other diseases such as diabetes mellitus (3).…”
Section: Introductionmentioning
confidence: 99%
“…AAPH is an azo compound and completely dissolved in alkyl, peroxyl and alkoxyl radicals at physiological temperature [11]. AAPH has been widely used to study the mechanism of oxidative stress [12,13]. In our previous experiments, the chick embryo on embryo development day (EDD) 9 was treated with a large dose of AAPH.…”
Section: Discussionmentioning
confidence: 99%